Reconciling Climate Change and Trade Policy - Mattoo, Aaditya; Subramanian, Arvind; van der Mensbrugghe, Dominique; He, Jianwu (2012)
There is growing clamor in industrial countries for additional border taxes on imports from countries with lower carbon prices. The authors confirm the findings of other research that unilateral emissions cuts by industrial countries will have minimal carbon leakage effects. However, output and exports of energy-intensive manufactures are projected to decline potentially creating pressure for trade action. A key factor affecting the impact of any border taxes is whether they are based on the carbon content of imports or the carbon content in domestic production. Their quantitative estimates suggest that the former action when applied to all merchandise imports would address competitiveness and environmental concerns in high income countries but with serious consequences for trading partners. For example, China s manufacturing exports would decline by one-fifth and those of all low and middle income countries by 8 per cent; the corresponding declines in real income would be 3.7 per cent and 2.4 per cent. Border tax adjustment based on the carbon content in domestic production, especially if applied to both imports and exports, would broadly address the competitiveness concerns of producers in high income countries and less seriously damage developing country trade.